THE INFLUENCE OF ECO-AIRPORT AND MALL-AIRPORT CONCEPTS AND CULTURAL DISPLAY OF EAST BORNEO ON VISITORS’ SATISFACTION AT SULTAN AJI MUHAMMAD SULAIMAN AIRPORT BALIKPAPAN - Saida Zainurossalamia Z.A.; Heksarini A.; Sudarsono S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2018)
This research aimed to analyze the influence of eco-airport and mall-airport concepts and cultural display of East Borneo on visitors’ satisfaction at Sultan Aji Muhammad Sulaiman Airport Balikpapan. The analysis tool was Smart-PLS 3.0 and the research method was quantitative method of path analysis. The result of the research showed that eco-airport and mall-airport concepts and cultural display of East Borneo had positive and significant influence on visitors’ satisfaction at Sultan Aji Muhammad Sulaiman Airport Balikpapan with the contribution of R-square value 78,3%.